1987
DOI: 10.1128/aac.31.11.1750
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal interactions of a beta-lactam and beta-lactamase inhibitors in experimental Pseudomonas aeruginosa endocarditis caused by a constitutive overproducer of type Id beta-lactamase

Abstract: We investigated the in vitro and in vivo effects of a combination of a 1-lactam (ceftazidime) and a P-lactamase inhibitor (dicloxacillin) The medical therapy in human cases of Pseudomonas aeraginosa endocarditis has been disappointing, particularly in aortic and mitral valve involvements (25,26). One of the limiting factors in this regard, as exemplified in human as well as experimental Pseudomonas endocarditis, has been in vivo development of antibiotic resistahce. Such resistances have been variably direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…This occurred more frequently with sulbactam (four of four strains tested) than it did with clavulanate (one of four strains tested). In contrast, Bayer et al (2) found no in vitro synergy between sulbactam or clavulanate plus ceftazidime for a constitutive class I 3-lactamase-overproducing strain of P.…”
Section: Methodsmentioning
confidence: 91%
“…This occurred more frequently with sulbactam (four of four strains tested) than it did with clavulanate (one of four strains tested). In contrast, Bayer et al (2) found no in vitro synergy between sulbactam or clavulanate plus ceftazidime for a constitutive class I 3-lactamase-overproducing strain of P.…”
Section: Methodsmentioning
confidence: 91%
“…Interestingly, it was previously reported for a model of rabbit endocarditis caused by a Pseudomonas aeruginosa strain that constitutively overproduced a cephalosporinase that the low efficacy of a combination of ceftazidime and dicloxacillin (used as a reversible inhibitor of the cephalosporinase) was due to the high density of bacteria present in the vegetation (2). A synergy between the ,-lactam (ceftazi-VOL.…”
Section: Methodsmentioning
confidence: 99%
“…A synergy between the ,-lactam (ceftazi-VOL. 34,1990 on May 12, 2018 by guest http://aac.asm.org/ Downloaded from dime) and the reversible ,B-lactamase inhibitor (dicloxacillin) was observed in vitro only at a low inoculum (105 CFU/ml), and it was suggested that at a high inoculum (107 CFU/ml), dicloxacillin was slowly hydrolyzed or rendered incapable of rebinding the enzyme (2).…”
Section: Methodsmentioning
confidence: 99%
“…Selected vegetations were processed for transmission electron microscopy (see below). All other vegetations from individual animals were pooled, weighed, homogenized in 0.5 ml of sterile saline, and then quantitatively cultured(5).Intravegetation bacterial densities were expressed as log1o CFU per gram of vegetations (+SD). Vegetations were considered culture negative if no growth occurred in subcultures of undiluted vegetation homogenates; however, for purposes of statistical comparisons, such culture-negative vegetations were considered to contain c2 log1o CFU/g because of the average size of vegetation undergoing homogenization (s0.01 g)(5).…”
mentioning
confidence: 99%